Three Steps Interview in Teaching Speaking Skill for EFL Learners - Laili Hendriani (Universitas Hamzanwadi, 2018)
This study aimed at examining the effectiveness of Three Steps interview in Teaching Speaking Skill for the tenth graders of MA Mu’allimat NW Pancor in the school year 2016-2017. The problems formulated in this study were (1) Is the Three Steps Interview effective in teaching speaking for the tenth graders of MA Mu’allimat NW Pancor in the school year 2016-2017? (2) How is the effectiveness of Three Steps Interview in teaching speaking for the tenth graders of MA Mu’allimat NW Pancor in the school year 2016-2017? This research applied pre-experimental design. The population was the tenth graders of MA Mu’allimat NW Pancor consisted of 7 classes. The present researcher took one class as the sample which consisted of 28 students in X IPA 2 as the experimental class. To collect the data, a pre-test and a post-test were given to the students for the tenth graders. To analyze the data, the present researcher applied SPSS 22 for windows. After submitting the data to paired sample t-test, the present researcher found that there was significant difference in the mean scores between the pre-test and the post test, t (df =27) = 16.5 at p .01, meaning that the null hypothesis was rejected and the alternative hypothesis was accepted. Three Steps Interview is significantly effective in teaching speaking for the tenth graders of MA Mu’allimat NW Pancor in the school year 2016- 2017. Considering the process and the results of this research, the present researcher suggests that the English teacher should use Three Steps Interview in Teaching Speaking.